An evaluation of methods for the determination of cation exchanges capacity. - Ismail, Jamilah; Ishak , Che Fauziah
The NH4OAc (pH7.0),leaching and shaking,BaCI2-TEA (pH8.2) and the Gillman compulsive exchange methods for the determination of cation exchange capacity (CEC) were evaluated. It was found that the NH4OAc (pH7.0),leaching and shaking methods gave comparable CEC values for most of the soils used. Of the methods selected,BaCI2-TEA (pH8.2) gave the highest CEC values and the Gillman methods,which was determined at the field pH and ionic strength,gave the lowest CEC values. From the correlation studies,the best correlation was obtained between the NH4OAc (pH7.0)and BaCI2-TEA (pH8.2)methods. There were no significant correlation between the Gillman method and the other three methods studied.